LAYANAN INFORMASI DALAM MENINGKATKAN PERENCANAAN KARIER ANAK ASUH PANTI ASUHAN - Thaheransyah; Dewita, Erna; Mustika Amri, Nadia; Desmaniar, Rani (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2023)
A career plan is a map that will guide each individual in determining his future goals. The absence of a career plan will have an impact on individual readiness to face the future, especially those related to the world of work. This is also experienced by foster children who live in orphanages, especially the Aisyiyah Orphanage in Padang City. Financially, foster children living in the Aisyiyah Orphanage in Padang City have the ability to pursue higher education. Because while they are in the orphanage they get special financing from the institution in the form of food, shelter and education financing. However, this potential has not been fully utilized by adolescents living in orphanages to plan their education to a higher level. Through this community service activity, it is expected to provide knowledge and understanding of the importance of career planning for orphanage adolescents. The purpose of community service is to improve the career planning of adolescents of the Aisyiyah Koto Tangah Timur Orphanage through the provision of information services. The implementation of this service is carried out using information service techniques through several stages, namely the stage of identifying information needs by finding and understanding what information is needed and relevant to the problems faced by the subject. Then the information collection stage is to collect information in accordance with the recipient's request. The needs of the subject can be known through observation, interviews, or other sources. Followed by the information evaluation stage, namely before conveying information to the recipient, an evaluation of the source of information is carried out, especially those related to validity, accuracy, and relevance to the needs of the subject. It is very important to ensure that the information to be conveyed can be useful for the resolution of problems experienced by the subject. The stage of organizing information, where information is arranged in a way that is easy to understand, logical and systematic so that the recipient can easily understand its content, so that the information provided can be absorbed properly by all members of the group who need the information. The feedback stage is a discussion session with information service participants related to messages that have been conveyed, especially those related to information that cannot be understood by service participants, so it is necessary to be given the opportunity to discuss to increase their understanding and knowledge related to the information conveyed. Finally, the evaluation stage is to evaluate the satisfaction of the recipient of the information, to measure whether the information provided is suitable for their needs and whether they can understand each information provided.